The N-terminal 14-mer model peptide of human Ctr1 can collect Cu(ii) from albumin. Implications for copper uptake by Ctr1. Issue 12 (29th November 2018) - Stefaniak, Ewelina; Płonka, Dawid; Drew, Simon C.; Bossak-Ahmad, Karolina; Haas, Kathryn L.; Pushie, M. Jake; Faller, Peter; Wezynfeld, Nina E.; Bal, Wojciech
Abstract : The superior Cu(ii ) affinity of human copper transporter 1 (hCtr1) drives copper acquisition from human serum albumin (HSA). Abstract : Human cells acquire copper primarily via the copper transporter 1 protein, hCtr1. We demonstrate that at extracellular pH 7.4 Cu II is bound to the model peptide hCtr11–14 via an ATCUN motif and such complexes are strong enough to collect Cu II from albumin, supporting the potential physiological role of Cu II binding to hCtr1.